Metabolomic Profiling of the Effects of Dapagliflozin in Heart Failure With Reduced Ejection Fraction: DEFINE-HF. Issue 11 (23rd May 2022) - Selvaraj, Senthil; Fu, Zhuxuan; Jones, Philip; Kwee, Lydia C.; Windsor, Sheryl L.; Ilkayeva, Olga; Newgard, Christopher B.; Margulies, Kenneth B.; Husain, Mansoor; Inzucchi, Silvio E.; McGuire, Darren K.; Pitt, Bertram; et al.
Abstract : Background: Sodium-glucose cotransporter-2 inhibitors are foundational therapy in patients with heart failure with reduced ejection fraction (HFrEF), but underlying mechanisms of benefit are not well defined. We sought to investigate the relationships between sodium-glucose cotransporter-2 inhibitor treatment, changes in metabolic pathways, and outcomes using targeted metabolomics. Methods: DEFINE-HF (Dapagliflozin Effects on Biomarkers, Symptoms and Functional Status in Patients With HF With Reduced Ejection Fraction) was a placebo-controlled trial of dapagliflozin in HFrEF. We performed targeted mass spectrometry profiling of 63 metabolites (45 acylcarnitines [markers of fatty acid oxidation], 15 amino acids, and 3 conventional metabolites) in plasma samples at randomization and 12 weeks. Using mixed models, we identified principal components analysis–defined metabolite clusters that changed differentially with treatment and examined the relationship between change in metabolite clusters and change in Kansas City Cardiomyopathy Questionnaire scores and NT-proBNP (N-terminal probrain natriuretic peptide). Models were adjusted for relevant clinical covariates and nominal P <0.05 with false discovery rate–adjusted P <0.10 was used to determine statistical significance. Results: Among the 234 DEFINE-HF participants with targeted metabolomic data, the mean age was 62.0±11.1 years, 25% were women, 38% were Black, and mean ejection fraction was 27±8%. Dapagliflozin increased ketone-related and short-chain acylcarnitine as well as medium-chain acylcarnitine principal components analysis–defined metabolite clusters compared with placebo (nominal P =0.01, false discovery rate–adjusted P =0.08 for both clusters). However, ketosis (β-hydroxybutyrate levels >500 μmol/L) was achieved infrequently (3 [2.5%] in dapagliflozin arm versus 1 [0.9%] in placebo arm) and supraphysiologic levels were not observed. Increases in long-chain acylcarnitine, long-chain dicarboxylacylcarnitine, and aromatic amino acid metabolite clusters were associated with decreases in Kansas City Cardiomyopathy Questionnaire scores (ie, worse quality of life) and increases in NT-proBNP levels, without interaction by treatment group. Conclusions: In this study of targeted metabolomics in a placebo-controlled trial of sodium-glucose cotransporter-2 inhibitors in HFrEF, we observed effects of dapagliflozin on key metabolic pathways, supporting a role for altered ketone and fatty acid biology with sodium-glucose cotransporter-2 inhibitors in patients with HFrEF. Only physiologic levels of ketosis were observed. In addition, we identified several metabolic biomarkers associated with adverse HFrEF outcomes. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02653482.